Risk Assessment Ambient Air Quality (NO2 And SO2) and The Respiratory Disorders to Communities in the Kalianak Area of Surabaya - Ani Masito (Universitas Airlangga, 2018)
Air pollutant gas that has a real impact on the respiratory system is NO2 and SO2. Kalianak Surabaya is one of the areas with high traffic density more than 1.500 vehicles every hour. The most affected communities are the people living along the Kalianak highway. This study aims to analyze the ambient air (NO2 and SO2) in Kalianak and the risk of respiratory distress in the surrounding community. This research is descriptive, with cross sectional approach. The sample of this research is 19 respondents was done by purposive sampling. Spirometers were used to determine the status of lung function. The variables studied were age, length of stay, smoking habit, and Body Mass Index. The collected data were analized with environmental health risk assessment. Environmental Health Risk Assessment showed that the people living in this area unsafe with concentration of NO2 as measured. The results showed that more than 50% of respondents have respiratory problems (68,4%) with the mayority of respondenst aged 46-55 years old (31,6%), leght of stay >20 years (47,4%), non smokers (47,4%), and normal Body Mass Index (36,8%). The conclusion from this research is ambient air quality (NO2 and SO2) in Kalianak Surabaya still meet the quality standard, and the RQ>1 for NO2, it means that the risk level is unsafe. It is recommended that there is an efforts to control air pollution caused by motor vehicle activity by planting planst that can reduce ambient air pollutants.